2016
DOI: 10.18632/oncotarget.7367
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MALAT1 increases AKAP-9 expression by promoting SRPK1-catalyzed SRSF1 phosphorylation in colorectal cancer cells

Abstract: Our earlier findings indicate that the long non-coding RNA MALAT1 promotes colorectal cancer (CRC) cell proliferation, invasion and metastasis in vitro and in vivo by increasing expression of AKAP-9. In the present study, we investigated the molecular mechanism by which MALAT1 enhances AKAP9 expression in CRC SW480 cells. We found that MALAT1 interacts with both SRPK1 and SRSF1. MALAT1 increases AKAP-9 expression by promoting SRPK1-catalyzed SRSF1 phosphorylation. Following MALAT1 knockdown, overexpression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…The MALAT1 gene is highly conserved across mammals, suggesting that it may have important biological implications [9]. Evidence suggests that MALAT1 may act like an oncogene in several malignancies, including lung cancer [17, 24], pancreatic cancer [19], liver cancer [20], bladder cancer [25], prostate cancer[26], colon cancer [27, 28], renal cell carcinoma [18], and oral squamous cell carcinomas [29, 30]. Lowering MALAT1 expression in hepatocellular carcinoma cells resulted in reduced cell proliferation and colony formation [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MALAT1 gene is highly conserved across mammals, suggesting that it may have important biological implications [9]. Evidence suggests that MALAT1 may act like an oncogene in several malignancies, including lung cancer [17, 24], pancreatic cancer [19], liver cancer [20], bladder cancer [25], prostate cancer[26], colon cancer [27, 28], renal cell carcinoma [18], and oral squamous cell carcinomas [29, 30]. Lowering MALAT1 expression in hepatocellular carcinoma cells resulted in reduced cell proliferation and colony formation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Lowering MALAT1 expression in hepatocellular carcinoma cells resulted in reduced cell proliferation and colony formation [20]. MALAT1 was also found to promote colon cancer cell proliferation, invasion and metastasis in vitro and in vivo by increasing AKAP-9 expression [28]. For breast cancer, suppressing MALAT1 expression led to increased differentiation of primary tumor cells and reduced metastasis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Derived from normal colon epithelial cells, colorectal cancer (CRC) has been regarded as a malignant cancer, which causes massive morbidity and mortality all over the world (Chubb et al, ; Hu et al, ). Millions of people suffer from the threat of CRC (Wang, Nie, Wu, Liu, & Guo, ; J. Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Such as, previous studies suggested that long non-coding RNA MALAT1 promoted tumor growth and metastasis by inducing epithelial-mesenchymal transition in oral squamous cell carcinoma [10]. MALAT1 increased AKAP-9 expression by promoting SRPK1-catalyzed SRSF1 phosphorylation in colorectal cancer cells [11]. Wang et al reported that MALAT1 promoted malignant development of esophageal squamous cell carcinoma by targeting β-catenin via Ezh2 [12].…”
Section: Introductionmentioning
confidence: 99%